Julian T. - A Studier of Rimbaud, Tuwim of Tykes, Tuwim for Children - Kuczyńska-Koschany, Katarzyna (Porównania, 2019)
Julian Tuwim (1894-1953) was a studier of Rimbaud in numerous ways: he read Jean Arthur Rimbaud (1854-1891) and translated his poems. He knew his poetry by heart and recited it. He worshiped the French poet and he visited his grave in Charleville and left him a bunch of red roses. He considered Rimbaud the greatest poet of all. Tuwim, probably, in the most interesting fashion assimilated and smuggled Rimbaud into his own poetry, at all its levels. Tuwim and Rimbaud are connected by what might be called the childishness of the poetic imagination. Both of them are literary rogues who are characterised by their creative disinvolture. Both of them advocate anarchy at a high artistic level.